REVIEW: ANIMAL SERUM REPLACEMENT IN MESENCHYMAL STEM CELLS CULTURE - Ariyani Noviantari (Jurnal Bioteknologi dan Biosains Indonesia, 2022)
Mesenchymal stem cells (MSCs) are being used in clinical applications and must comply with Good Manufacturing Practices (GMP) standards and The National Agency of Drug and Food Control (NA-DFC)) regulations. MSCs cultured using a culture medium and added with several supplements like animal serums. However, animal serums can be a source of virus transmission. Therefore, it is necessary to substitute supplements for the animal serum that are safe to use in cell therapy using MSCs. The paper discusses substituting animal serum MSCs culture. This paper is a literature review through a literature search in scientific journals and research reports that explains the various studies on free serum in the culture of MSCs. It can be concluded that human platelet lysate (hPL), human platelet-rich plasma (hPRP), human serum (hS), human umbilical cord serum/plasma (hUCS/P), or human plasma-derived supplement for cell culture medium (SCC) can be used as substitutes for animal serum in MSCs culture.